Influence Work-Life Balance on Job Satisfaction and Productivity of Millennial Employees at PT. Berca Hardiaperkasa Luwuk Southeast Sulawesi - Hardy Rony Nayoan; Citra Dewi Indrawati; Muh. Fikri Dari; Moh . Gifari Sono (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2024)
Work-life balance is one of the key factors in improving employee well-being and performance, especially for millennials who have high expectations of work flexibility. This study aims to analyze the effect of work-life balance on job satisfaction and productivity of millennial employees, with employee engagement as a mediating variable. The results show that work-life balance has a positive and significant effect on job satisfaction and employee productivity, with a stronger effect on productivity. In addition, work-life balance also has a very large influence on employee engagement, which means that employees with a good work-life balance will be more engaged in their work. Employee engagement itself was shown to have a positive and significant effect on job satisfaction and employee productivity, confirming that employees who feel emotionally and cognitively engaged in their work tend to be more satisfied and more productive. Furthermore, employee engagement was also shown to mediate the effect of work-life balance on job satisfaction and employee productivity, but this mediating effect was stronger on productivity than on job satisfaction. The findings of this study confirm that work-life balance plays an important role in improving millennial employees' satisfaction and productivity, with employee engagement as an intermediary factor that strengthens the relationship